Regional and temporal progression of atrial remodeling in angiotensin II mediated atrial fibrillation - Jansen, Hailey J.; McRae, Megan D.; Mackasey, Martin; Rose, Robert A. (Frontiers in Physiology, 2022)
Atrial fibrillation (AF) is associated with electrical and structural remodeling in the atria; however, the regional and temporal progression of atrial remodeling is incompletely understood. The objective of this study was to investigate the regional and temporal progression of atrial remodeling leading to changes in AF susceptibility in angiotensin II (Ang II) mediated hypertension. Mice were infused with Ang II for 3, 10 or 21 days. AF susceptibility and atrial electrophysiology were studied in vivo using intracardiac electrophysiology. Right and left atrial myocyte electrophysiology was studied using patch-clamping. Atrial fibrosis was assessed histologically. P wave duration and atrial effective refractory period increased progressively from 3 to 21 days of Ang II. AF susceptibility tended to be increased at 10 days of Ang II and was elevated at 21 days of Ang II. Left, but not right, atrial AP upstroke velocity and Na+ current were reduced at 10 and 21 days of Ang II. Left atrial action potential (AP) duration increased progressively from 3 to 21 days of Ang II due to reductions in repolarizing K+ current. Right atrial AP prolongation was increased only after 21 days of Ang II. Left and right atrial fibrosis developed progressively from 3 to 21 days, but increases were larger in the left atrium. In conclusion, Ang II mediated atrial electrical and structural remodeling develop earlier and more extensively in the left atrium compared to the right atrium, providing insight into how atrial remodeling leads to enhanced AF susceptibility in Ang II mediated hypertension.